Kondisi Terumbu Karang di Perairan Gili Gede, Sekotong Lombok Barat - Nurliah Buhari; Mahardika Rizqi Himawan; Edwin Jefri (Program Studi Ilmu Kelautan, Jurusan Perikanan dan Ilmu Kelautan, Fakultas Pertanian, Universitas Mataram, 2021)
Protection and sustainable data collection are very important in order to protect the coral reef ecosystem. This research was conducted to monitor and determine the condition of coral reefs in the eastern part of Gili Gede Island, which is administratively located in Sekotong Sub-District, West Lombok Regency, NTB. The method used is Line Intercept Transect (LIT). Furthermore, the starting point of the transect stretch is recorded using GPS coordinates and the depth gauge is used to estimate the depth of the water. The results showed that the status of coral reefs tended to be badly damaged with the mean value of all stations (21.92%). Fishery activities and pressure from the land are thought to be several factors that tend to affect the poor coastal ecosystem